Of passionate curves and desirable cadences : themes on Waiwai social being - Mentore, George P. (University of Nebraska Press ; Combined Academic [distributor], 2005)
Compelling and evocative, Of Passionate Curves and Desirable Cadences reveals the vital cultural interconnections at the heart of a rain-forest Amerindian society. The Waiwai, who live in the remote interior of Guyana and in neighboring Brazil, follow a customary subsistence lifestyle built around swidden agriculture and hunting.